Learning Transfer Perceived from the Baldwin & Ford Theory: An Empirical Study on the Alumni of Pre-Service Training in East Java - Esti Sri Rahayu; Andi Paerah (Enrichment : Journal of Management, 2022)
One of the education and training in the environment of Civil State Apparatus, which is the pre-service training aimed for civil servant candidates who need to obtain post-training review, because it is an effective application, andit is certainly sustainable from the knowledge and skills which have been obtained after training.The aim of this study is to understand characteristic aspects of learners, training design and work environment in affecting learning transfer of the alumni of Pre-service Training Class III in East Java. The method of the study uses qualitative approach with indepth interview toward 5 informants who have enrolled in the training in 2015 and 2016. The result of the study shows that (1)motivation and self-efficacyare characteristic factors of learners which can be intervened, with the learners can be conditioned by goal setting, which is by the existence of a value internalization process and verbal persuasion which later can boost the learners’ motivation and self-efficacy, (2) the training intervention does not stop only on the variables of learning outcome and retention, but it is integrated to enter the area of transfer condition (transfer outcome).